Evaluasi Prestasi Atlet Wushu Koni Kota Medan Tahun 2014 - Novita Novita (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2015)
The purpose of this study was to evaluate the results of Wushu athlete's performance KONI Medan through match-Week Sports Medan and the results of physical tests in 2014. The study was conducted at the Yayasan Kusuma Wushu Indonesia and Faculty of Sport Sciences, State University of Medan. The total population of 13 athletes Wushu, Sampling using purposive sampling technique which has been determined by KONI Medan condition in order to obtain 13 athletes who are the target of Wushu Athletes selection results KONI Medan City Sports Week 2013. This study used a descriptive analysis to analyze research data obtained. The results of this study are: 1) Wushu Athletes KONI Medan has a total test results overall with an average of less well categorized.